MENINGKATKAN KEMAMPUAN MOTORIK HALUS DENGAN MENGGUNAKAN MEDIA PRE WRITING BOARD PADA ANAK DISABILITAS INTELEKTUAL - Siska Afriani; Zulmiyetri Zulmiyetri; Damri Damri; Safaruddin Safaruddin; Rila Muspita (STKIP Pesisir Selatan, 2025)
This study aimed to improve the fine motor skills of children with intellectual disabilities through the use of Pre-Writing Board media in pre-writing learning activities for second-grade students at SLB Amanah Koto Tangah. The research employed Classroom Action Research consisting of two cycles, each comprising the stages of planning, action implementation, observation, and reflection. The research subjects were two students with the initials AP and CI. Data were collected through structured observation, documentation, and fine motor skill tests, while data analysis used percentage techniques to identify improvements in each cycle. The results showed a continuous improvement in the fine motor skills of both subjects. The initial abilities of AP and CI were 51% and 38%, respectively. After the implementation of Cycle I, the abilities increased to 70% for AP and 60% for CI. More optimal improvement occurred in Cycle II, in which AP reached 84% and CI reached 75%. The novelty of this study lies in the utilization of Pre-Writing Board as a structured, concrete, and practical pre-writing learning medium that aligns with the learning characteristics of children with intellectual disabilities.